Advances in the treatment of bleeding disorders. (19th October 2016) - Peyvandi, F.; Garagiola, I.; Biguzzi, E.
Summary: Historically, the bleeding episodes in subjects with coagulation disorders were treated with substitution therapy, initially with whole blood and fresh frozen plasma, and more recently with specific factor concentrate. Currently, patients with hemophilia have the possibility of choosing different effective and safe treatments, including novel extended half‐life and alternative hemostatic drugs. The availability of novel extended half‐life products could probably overcome current prophylaxis limitations, particularly in hemophilia B patients, by reducing the frequency of injections, achieving a higher trough level, and improving the quality of life of the patients. In addition, subcutaneous administration of alternative therapeutics would simplify prophylaxis in patients with hemophilia A and B with and without inhibitors. Regarding von Willebrand disease, a recombinant von Willebrand factor was recently developed to control bleeding episodes in patients with this disease, in addition to available von Willebrand factor/factor VIII concentrates. The management of patients affected by rare bleeding disorders (RBDs) is still a challenge, owing to the limited number of specific products, which are mainly available only in countries with high resources. Some improvements have recently been achieved by the production of new recombinant factor (F) XIII A subunit‐derived and FX plasma‐derived products for the treatment of patients affected by FXIII and FX deficiency. In addition, the development of novel alternative therapeutics, such as anti‐tissue factor pathway inhibitor, ALN‐AT3, and ACE910, for patients with hemophilia might also have a role in the treatment of patients affected by RBDs.